ANALISIS DAYA TAMPUNG AIR PADA SALURAN DRAINASE DI LINGKUNGAN ART CENTRE KOTA DENPASAR - Anak Agung Ratu Ritaka Wangsa; Ida Bagus Suryatmaja; A A Meri Puja Andini (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2023)
Flood is a natural event that can have a negative impact, for example, causing health problems and the safety of living things. The drainage channel studied in this study is the Tukad Kelandis River which stretches from Jl. Katrangan to Jl. Nusa Indah which crosses the Denpasar City Art Center. In 2021 there was a flood at the Art Center, the impact was flooding under the Ksiranawa Building where the art exhibition was held. For this problem, it is necessary to conduct a study (research) on the profile of the flood front as a flood prevention measure. Before modeling the water level profile with HEC-RAS, when estimating the capacity of the drainage channel, a quantitative method must be calculated, namely by measuring the condition of the canal in the case study. From the results of flood simulations with return times of 2, 5, 10, 20 and 25 years. The results of the evaluation of the current channel discharge at all points of the channel experienced flooding with return periods of 2, 5, 10, 20 - 25 years because the results of the current channel discharge and water level exceeded. The profile is shown in the results at all channel points where the sum of the actual water level (E.G., level) and water level feet (W.S. level) is greater than the capacity of the water discharge in the channel. In addition, at the water level (Crit. W.S.) in the Sta. 2 is 5.05 m, which is less than (W.S. level) which is 6.69 m, so the flow is supercritical.